The requirements to enhance the design of context-aware mobile patient monitoring systems using wireless sensors - Al-Bashayreh, Mahmood Ghaleb; Hashim, Nor Laily; Khorma, Ola Taiseer (Springer Berlin Heidelberg, 2013)
Designing and developing Context-aware Mobile Patient Monitoring Systems (CMPMS) using wireless sensors are emerging in the biomedical informatics domain.However, previous studies related to this topic are fragmented.In fact, the literature has no standard types and sources of context information.These types and sources are required to design such systems.In addition, there is no standard context reasoning approach to facilitate the development of these systems.To address these absences, this paper is a survey of the CMPMS in the biomedical informatics to identify potential types and sources of context information as well as the context reasoning approaches that are required to be addressed in designing and developing such systems. The results are expected to help researchers to enhance the design and facilitate the development of CMPMS.